Analisa Nilai Produksi Ikan Laut Basah Selama 2016 – 2020 di Kabupaten Bima - Nur Habibah (Journal of Fisheries and Marine Applied Science, 2023)
Fisheries are among the leading resources in the Bima District area. This is because of aquaculture and capture fisheries. This condition is caused by the Bima district area being surrounded by the Indian Ocean, Flores Sea, and Sape Strait waters. Therefore, this study aimed to determine the production value of fresh seawater fish in the Bima district area and the SLS value. Observations were made by analyzing data on wet sea fish production value in each sub-district during 2016 – 2020. Data were obtained from the Bima Regency Maritime Affairs and Fisheries Service. From the observation results, it was found that the water fish production value was obtained in the Sape Sub District at 231957.21 tons and the lowest was in the Parado Sub-District which was 55694.1 tons. Meanwhile, if the sales value of fresh seawater fish, only Sape Sub-District has a sales value of IDR 1,033,373,551,615 and at the same time is the highest value compared to other sub-districts with sales values below IDR 200,000,000.